Prosedur Pengurusan Keberangkatan Kapal pada Kantor Satuan Pelayanan di Pelabuhan Penyeberangan Singkil: Penelitian - Meriah Kita Deliani; Dio Fany Pratama (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the administrative and operational procedures governing ship departure and arrival at the Singkil Ferry Port Service Unit (Satpel), Aceh, Indonesia. The research aims to analyze the sequence of administrative, technical, and inter-agency coordination processes involving the Harbourmaster, vessel operators, Quarantine Office, Customs, and the Water Police to ensure safe, secure, and efficient maritime operations. Data were collected through field observations and document analysis within the operational environment of Singkil Ferry Port. The findings indicate that the effectiveness of vessel clearance services is strongly influenced by the quality of coordination among agencies and the completeness of vessel documentation. Common delays are primarily caused by insufficient discipline among vessel operators in submitting required documents and by limited system integration among institutions. These issues result in slower processing times and reduced operational reliability. The study recommends enhancing operator compliance through stricter monitoring, improving the digitalization of administrative procedures, and strengthening human resource capacity within the Satpel. These measures are expected to streamline clearance processes, minimize delays, and uphold maritime safety standards.